Цифровий маркетинг в аграрному бізнесі: електронна комерція, соціальні мережі та онлайн-продажі сільськогосподарської продукції - Кобернюк, Сергій Олександрович; Koberniuk, Sergey; Яценко, Олександр Володимирович; Yatsenko, Oleksandr; Помазан, Ліна Миколаївна; Pomazan, Lina (Дніпровський державний аграрно-економічний університет, 2024)
У статті досліджено використання цифрового маркетингу в аграрному бізнесі. Охарактеризовано основні поняття: аграрний маркетинг і цифровий маркетинг. Розглянуто використання основних інструментів цифрового маркетингу в аграрному бізнесі (E-mail-маркетинг, контент маркетинг, маркетинг у соціальних мережах, вхідний маркетинг, Affiliate Marketing, веб-сайт, автоматизація маркетингу). Досліджено рівень розвитку інформаційно-комунікаційних технологій країн за індексом мережевої готовності. Визначено найбільш прибуткове сільськогосподарське підприємство – ТОВ «Вінницька птахофабрика». Проведено аналіз ефективності функціонування сайту найприбутковішого підприємства. Здійснено SEO-аудит веб-сайту досліджуваного підприємства. Зроблено контент-аналіз сайту підприємства. Досліджено використання SMM маркетингу (використання соціальних мереж Фейсбук, Інстаграм, Ютуб) та UGC-маркетингу підприємством. Розглянуто використання штучного інтелекту на підприємстві. Підведено підсумки про необхідність удосконалення роботи сайту підприємства з метою здійснення електронної комерції. Increasing the efficiency of innovative development of agrarian business requires the use of modern information and communication technologies for the organization and management of economic activity, automation and robotization of agro-industrial production. In the conditions of globalization and the deepening of inter-industry relations, the agricultural sector has become a basic innovative component that forms trends in the growth of the efficiency of adjacent industries, therefore the digitalization of the agricultural sector is extremely important for improving the efficiency of communications between the producer and the consumer. The article examines the use of digital marketing in agricultural business. The main concepts are characterized: agricultural marketing and digital marketing. The use of the main tools of digital marketing in agricultural business (E-mail marketing, content marketing, marketing in social networks, inbound marketing, Affiliate Marketing, website, marketing automation) is considered. The level of development of information and communication technologies of the countries according to the network readiness index was studied (Ukraine ranks 43rd). The most profitable agricultural enterprise was determined - Vinnytsia Poultry Farm LLC. An analysis of the effectiveness of the website of the most profitable enterprise was carried out. An SEO audit of the website of the company under investigation was carried out. A content analysis of the company’s website was made. The use of SMM marketing (use of social networks Facebook, Instagram, YouTube) and UGC marketing by the enterprise was studied. The use of artificial intelligence at the enterprise is considered. Summarized on the need to improve the operation of the company’s website for the purpose of e-commerce: supplement the content of the site with content with relevant requests, add images and videos, make internal SEO optimization of the site, improve the quality of the material posted on the site, improve interaction with real users of the site through social networks, advertising, subscriptions, newsletters, etc., increase the sources of traffic to the site through the use of advertising, commercial requests, messengers, link building, webinars, QR codes, SMS and email.
Digital marketing in agribusiness: e-commerce, social networks and online sales of agricultural products
Keywords: цифровий маркетинг; digital marketing; аграрний маркетинг; agricultural marketing; SMM; SMM; SEO-аудит; SEO audit; контент-маркетинг; content marketing; UGC-контент; UGC content; штучний інтелект; artificial intelligence